Early career teacher peer support through private groups in social media. Issue 1 (1st January 2018) - Mercieca, Bernadette; Kelly, Nick
ABSTRACT: This paper describes the support that Australian early career teachers are accessing through private groups within social media. It presents findings from 22 interviews with teachers who indicated that Facebook was a source of support. Participants describe using private online groups for: (a) support during casual employment; (b) accessing collegial support from pre-existing connections, in particular those formed during initial teacher education; and (c) support to deal with challenging situations such as a hostile work environment. The paper suggests that further research needs to be conducted into how private media groups might support the needs of early career teachers.